Macrophages release IL11-containing filopodial tip vesicles and contribute to renal interstitial inflammation - Xiaodong Zhu; Yu Zhao; Yuqiu Liu; Wen Shi; Junlan Yang; Zhihong Liu; Xiaoliang Zhang (Cell Communication and Signaling, 2023)
Abstract Macrophage filopodia, which are dynamic nanotube-like protrusions, have mainly been studied in the context of pathogen clearance. The mechanisms by which they facilitate intercellular communication and mediate tissue inflammation remain poorly understood. Here, we show that macrophage filopodia produce a unique membrane structure called “filopodial tip vesicle” (FTV) that originate from the tip of macrophages filopodia. Filopodia tip-derived particles contain numerous internal-vesicles and function as cargo storage depots via nanotubular transport. Functional studies indicate that the shedding of FTV from filopodia tip allows the delivery of many molecular signalling molecules to fibroblasts. We observed that FTV derived from M1 macrophages and high glucose (HG)-stimulated macrophages (HG/M1-ftv) exhibit an enrichment of the chemokine IL11, which is critical for fibroblast transdifferentiation. HG/M1-ftv induce renal interstitial fibrosis in diabetic mice, while FTV inhibition or targeting FTV IL11- alleviates renal interstitial fibrosis, suggesting that the HG/M1-ftv IL11 pathway may be a novel mechanism underlying renal fibrosis in diabetic nephropathy. Collectively, FTV release could represent a novel function by which filopodia contribute to cell biological processes, and FTV is potentially associated with macrophage filopodia-related fibrotic diseases. Video Abstract